The emergence of new uses for rural spaces and interrelations of rural and urban labour markets - Thomas Dax (European Regional Science Association (ERSA), 1998)
38th Congress of the European Regional Science Association 28 August ? 1 September 1998 in Vienna Europe quo vadis? ? Regional question at the Turn of the Century Topic: E: Poverty, Labour Markets and Migrations The emergence of new uses for rural spaces and interrelations of rural and urban labour markets (Abstract) by Thomas Dax, Bundesanstalt fur Bergbauernfragen The former rural-urban dichotomy has been rejected be recent analyses of economic performance of rural areas. Much of this new reading of spatial tendencies within the industrialised world has been influenced by the rising concern for rural areas and the search for comparative data and concepts at international level. With accelerated spatial and cultural integration the debate on rurality has questioned the specificity of rural areas as a distinctive theoretical concept at all. The paper takes the concept elaborated by the OECD-Group of the Council on Rural Development as starting point which dismisses the notion that there are clear cut boundaries between such territorial concepts as urban and rural areas. By setting up a hierarchical territorial scheme it elucidates the linkages of "rural? and "urban? parts of the territory at local and regional levels. Taking account of the spread of new technologies, especially information and communication technologies and the effects of globalisation of key elements of economy and culture our former understanding of rather narrow forms of interactions have to be reconsidered. Networking seems to become one of the central requirements for development replacing sectoral/single objective support schemes. The paper will show that a differentiation into lagging and dynamic rural regions is needed to reflect the actual very diverse development of these parts of the territories. The regional level which corresponds roughly to labour market regions can be split up into its rural and urban parts. This enables not to stick just to an assessment of inter-regional relations but to show also the intra-regional patterns of population, labour and capital flows. Due to rather low settlement mobility and as a consequence high commuting shares Austria provides an example where population and employment development in rural areas are often different. This gap in regional performance underlines the need for deeper regional analysis and case-by-case assessment of the strengths and weaknesses, the scope and interrelations to other territories. The paper shall focus on the theoretical base addressing key issues as employment tendencies and the recognition of various forms of social exclusion being influenced by tendencies towards a splitting-up of job involvement among active populations. Taking account of these trends presents a prime requirement also for rural development policy. It shall also elaborate on case studies exemplifying the threat to development for rural areas in Austria and Europe. As rural areas would be conceived in the latest European discussion as territories offering highly demanded amenities rural development policies will have to harness these potentials. It will be of crucial importance to find ways to make use of these emerging new tasks of rural areas for the local/regional population so as to prevent larger groups of population from being excluded.
Keywords: 330